"Troubled Waters" impact study: student environmentalism in the Red Cedar River Basin - Fox, Christopher (My University, 2013)
As a research initiative by the University of Wisconsin-Stout and the Tainter Menomin Lake Association, Minnesota's Bell Museum of Natural History's acclaimed documentary film Troubled Waters: A Mississippi River Story was distributed to many of the high schools and middle schools of the Red Cedar River Basin, located in West Central Wisconsin. Upon the film screenings at the various high schools and middle schools, post-screening surveys were distributed immediately afterward. The purpose of the surveys was to assess the film's impact on students, as well as how it may influence environmental consciousness and individual and/or cooperative action in addressing environmental problems, specifically regarding phosphorus and nitrate pollution. There were 486 surveys in the initial sample size, which yielded some significant findings. Upon watching the documentary, demographic variables of gender, residence, school, age, and occupation revealed the overarching dominance of individualism over collective action in terms of respondents' potential sustainability initiatives
Keywords: Phosphorus pollution; Water quality; Red Cedar Basin; Cooperation; Individualism; Mississippi River--Environmental aspects; Agricultural pollution--Mississippi River; Nutrient pollution of water--Mississippi River; High school students--Wisconsin--Attitudes.; Middle school students--Wisconsin--Attitudes